2021
DOI: 10.3201/eid2709.210774
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 from Human to Domestic Ferret

Abstract: N atural infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in domestic animals living in infected households have been reported (1). Because of their increased popularity as a pet (2), domestic ferrets (Mustela putorius furo) pose a high risk for transmitting anthropozoonotic infections. A recent study in Spain showed that natural SARS-CoV-2 infections can occur in ferrets kept as working animals for rabbit hunting, especially if a high viral circulation is present in the human popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…Table 8 presents the results regarding the correlation between the fluorescence value (Fluor) of UMELISA SARS-CoV-2 Antigen and cut-off index (COI) of STANDARD F COVID-19 Ag FIA with the cycle threshold (Ct) of RT-PCR. Interpreting diagnostic test values for COVID-19 is essential for clinicians, epidemiologists and microbiologists [20][21][22][23][24][25]. Ct is a semiquantitative value inversely related to the amount of RNA in the sample, so that a low Ct number is related to higher viral load and vice versa [4,5,12,15,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Table 8 presents the results regarding the correlation between the fluorescence value (Fluor) of UMELISA SARS-CoV-2 Antigen and cut-off index (COI) of STANDARD F COVID-19 Ag FIA with the cycle threshold (Ct) of RT-PCR. Interpreting diagnostic test values for COVID-19 is essential for clinicians, epidemiologists and microbiologists [20][21][22][23][24][25]. Ct is a semiquantitative value inversely related to the amount of RNA in the sample, so that a low Ct number is related to higher viral load and vice versa [4,5,12,15,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, SARS-CoV-2 has been detected in minks in hundreds of mink farms in 14 countries ( Figure 2 ). Other pet animals, including domestic ferrets and hamsters, also tested positive in Slovenia in November 2020 and in China in January 2022, respectively [ 19 , 20 ]. Other than domestic, captive, and farmed animals, SARS-CoV-2 in wild animals including deer, feral minks, feral cats, and wild otters were reported in the USA, Spain, the Netherlands, and Spain, respectively [ 21 , 22 , 23 , 24 ] ( Figure 1 ).…”
Section: Sars-cov-2 Infection In Animalsmentioning
confidence: 99%
“…Since the first case of animal infection with SARS-CoV-2 in 2020, much effort has been put into tracking the infection sources in animals, which is the key to controlling infection in them. Several lines of evidence suggest that infection in dogs [ 11 , 16 , 26 , 27 ], cats [ 9 ], large cats [ 7 , 8 , 12 , 13 ], and domestic ferrets [ 19 ] were due to human-to-animal transmissions ( Figure 1 ). In the case of the farmed minks, it was reported that minks were infected through a human-to-mink transmission route [ 18 ]; then, infected minks transmitted the virus back to humans [ 28 ] ( Figure 1 ).…”
Section: Sars-cov-2 Transmission Routesmentioning
confidence: 99%
“…SARS-CoV-2 and its descendent variants have a wide host range besides humans. Natural human-to-animal infections have been documented in companion (dogs, cats, ferrets), [1][2][3] zoo (feline species 4 and gorillas), farmed (mink), 5 and wild (white-tailed deer) 6 animals. Experimental challenge has identified that non-human primates, hamsters, ferrets, American minks, cats, dogs, raccoon dogs, North American deer mice, Egyptian fruit bats, Asian small clawed otters, and white-tailed deer were highly susceptible to SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%